Substitusi Bekatul pada Tepung Tapioka untuk Pembuatan Flake: Kajian Terhadap Sifat Fisikokimia dan Sensoris - Magdalena Puspita Dewi, Adrianus Rulianto Utomo, Erni Setijawati, (Jurnal Teknologi Pangan dan Gizi, 2007)
A research on substitution of milk fat with red palm oil in Milk Powder (MP) production has been conducted. The aim of this research was to investigate the effects of corn oil substitution with red palm oil on physical, chemical and nutritional properties of the recombined milk powder (RMP). Pre-formulated milk powder (PMP) was prepared by mixing of corn oil, skim milk powder, stabilizer and water followed by filtering, preheating, homogenization and spray drying. The corn oil was substituted with 0, 25, 50, 75 and 100% of red palm oil (RPO-0, RPO-25, RPO-50, RPO- 75 and RPO-100). RMP formula were prepared as a commercial milk powder formula with protein and fat content of 20% and 18%, respectively. Chemical and physical properties of the RMPs were analyzed. The RMPs were then reconstituted and sensory character as well as nutritional properties was examined. The result showed that substitution of 50% corn oil with red palm oil resulted in a red palm oil milk powder (RPOMP) similar to the corn oil milk powder (control milk powder) in term of panelist acceptability. This RPOMP have a higher wet ability and solubility index but lower dispersibility and similar density to the control milk powder. The RPOMP contain a lower total and beta carotene content but higher tocoferol content than the control milk powder. Spray drying in the pre-formulated milk powder processing decrease 90% of carotene content of the pre-formulated milk powder but the tocoferol content was not affected by the process. In Wistar rats, consumption of RPOMP for 4 weeks had no effects on the lipids profiles.